Esio Trot - Dahl, Roald; Blake, Quentin (New York : Viking, 1990)
Shy Mr. Hoppy devises a plan to win the heart of his true love by teaching her a spell to make her tortoise grow bigger.
School Library Journal
Booklist
Bulletin (Center for Children's books)
6.0
3-6
3-6
Keywords: Turtles -- Fiction; Size -- Fiction; Turtles -- Fiction; Size -- Fiction; Magic -- Fiction